Misfitting the Research Process: Shaping Qualitative Research "in the Field" to Fit People Living With Dementia. (7th January 2020) - Webb, Joseph; Williams, Val; Gall, Marina; Dowling, Sandra
It is increasingly recognized that people living with dementia should be included in qualitative research that foregrounds their voices, but traditional research approaches can leave less room for flexibility than is necessary. This article builds on others who have examined the challenges and rewards of the qualitative research process with people living with dementia. With reference to a specific project on communication and dementia, the research design adaptations needed at each step to turn a "misfit" into a "fit" are examined. Misfitting, as a concept related to social practice theories, is used to argue the need for a coproduced and flexible approach to research design and data collection. Recommendations include being willing to adapt research methods, data collection locations, and aims of the project to fit participants' competencies, preferences, and realities; spending sufficient time getting to get to know staff and potential participants to build relationships; working round care practices and routines to minimize disruption; and using observational/visual methods can help include people living with dementia at each stage. People with dementia require researchers in the field to be creative in their methods, reflexive in their approach, and person-centered in their goals. Those adaptations can fundamentally change the ways in which the social practice of research is shaped.